Performance Of State Civil Apparatus: Intervening Effects Of Organizational Commitment And Work Motivation - Muhammad Ikram Idrus; Muhammad Islah Idrus (STMIK Dharma Wacana, 2024)
The performance of an employee in a government agency can be known from the results of a job which can be shown by the degree of the employee's ability to complete a job. The purpose of this study is toanalyze the direct influence of competence on organizational commitment, work motivation and employee performance of the South Sulawesi Provincial Marine and Fisheries Service both directly and indirectly. The type of research used is a quantitative research method with data collection using a questionnaire. This research was conducted using a survey approach and distributing questionnaires to analyze facts and data that support the information needed to support the discussion of the research. Thecausal relationship between the variables was obtained through hypothesis testing using SPSS and SmartPLS. The results showed that partially, competence has a positive and significant effect on organizational commitment, work motivation and employee performance. Furthermore, organizational commitment has an insignificant effect on employee performance while work motivation has a positive and significant impact on employee performance . As for indirect influence , it shows that organizational commitment has an insignificant effect when used as a mediating variable the influence of competence on performance while motivation is able to show positive and significant influence when used as a mediating variable